Whiteheadian Societies as Open-Ended Systems and Open-Ended Systems as Whiteheadian Societies - Bracken, Joseph A. (Process studies, 2012)
In this essay I defend two interrelated theses. The first is that Whiteheadian structured societies are best understood as open-ended systems akin to those currently being proposed in the natural and social sciences by Stuart Kauffman, David Sloan Wilson, and Niklas Luhmann. The second is that an open-ended system is best understood in terms of an ongoing interplay of subjectivity and objectivity, which I derive from a modest rethinking of the workings of a Whiteheadian structured society.